2006
DOI: 10.1116/1.2382949
|View full text |Cite
|
Sign up to set email alerts
|

Time of flight secondary ion mass spectroscopy investigation of ultralow-k dielectric modifications in hydrogen and deuterium plasmas

Abstract: Photoresist stripping processes based on hydrogen reductive chemistry have emerged as attractive replacements of the conventional treatments performed using O 2 plasma. H 2 discharges and plasma processes based on gas mixtures containing H 2 provide, in fact, adequate stripping rates while reducing the chemical modifications of the porous ultralow-k ͑ULK͒ dielectric materials employed in interconnect technology. In this work the authors investigate the chemical modification of a number of organosilicate low-k … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 19 publications
1
18
0
Order By: Relevance
“…Worsley et al suggest that, at elevated temperatures, the concentration of H species chemisorbed at the surface decreases due a lower sticking coefficient and that the material modification is strongly dependent on the porosity rate and the interconnectivity of the pores. 21 As for Lazzeri et al, 28 the chemical damage introduced by H 2 -based discharges depends strongly on the formulation of the organosilicate material. The substrate temperature is also seen to affect the influx of plasma species ͑extent of material modifications͒.…”
Section: B H 2 Plasmamentioning
confidence: 92%
See 1 more Smart Citation
“…Worsley et al suggest that, at elevated temperatures, the concentration of H species chemisorbed at the surface decreases due a lower sticking coefficient and that the material modification is strongly dependent on the porosity rate and the interconnectivity of the pores. 21 As for Lazzeri et al, 28 the chemical damage introduced by H 2 -based discharges depends strongly on the formulation of the organosilicate material. The substrate temperature is also seen to affect the influx of plasma species ͑extent of material modifications͒.…”
Section: B H 2 Plasmamentioning
confidence: 92%
“…wSi -O -Si w + 2H → w Si -H + Si -OH ͑⌬H r = + 42 kj mol −1 at 298 K͒, ͑4͒ 21,25,26,28 All these studies point out that the film modification is temperature dependent and is also correlated to the density of the H reactive species concentration in the plasma. 21 The film damage is minimized by increasing the substrate temperature, 25,26 while the damage is amplified with the reactive species concentration.…”
Section: B H 2 Plasmamentioning
confidence: 99%
“…In the case of ashing chemistries, static TOF-SIMS was used to study the nature of the top surface, while dynamic TOF-SIMS provided additional information concerning the lack or presence of additional damage in the bulk of the dielectric material. 54,55 Similarly, the mechanism of fluorocarbon-based etch plasmas could be established using static SIMS, 56,57 while confirming bulk dielectric damage in the form of carbon depletion by dynamic SIMS. Minimum plasma damage and pore sealing by oxygen-free fluorocarbon plasmas could also by corroborated using TOF-SIMS among other characterization techniques.…”
Section: Time-of-flight Secondary Ion Mass Spectrometry (Tof-sims)-tmentioning
confidence: 99%
“…Recently, the PCA was applied to study changes of ULK films after plasma in combination with ToFSIMS. 14 It is shown that the amount of carbon loss due to plasma treatments is visualized by typical FTIR peaks ͑Si-CH 3 , Si-C, C-Si-O, and Si-O-Si cage/network͒. Here, PCA was used to study structural bond change, since this method is sensitive variations of FTIR peaks.…”
Section: Introductionmentioning
confidence: 99%